Influence of Water Absorption on Mechanical and Morphological Behaviour of Roystonea-Regia/Banana Hybrid Polyester Composites - Rajamudi Gowda, Anand Hassan; Goud, Govardhan; Sathynarayana, Karthik; Puttegowda, Madhu (Applied Science and Engineering Progress, 2024)
This study investigated the properties of hybrid composites made from Roystonea-Regia and banana fibers for potential applications in industries requiring lightweight, environmentally favorable, and mechanically strong materials. The analysis of density and void fraction revealed that the addition of banana fibers increased the composite's density, despite the fact that the actual density was slightly lower than the theoretical density due to confined gases during fabrication. The results of tensile tests revealed that water absorption negatively affected tensile strength, whereas alkali treatment and hybridization enhanced performance. The composition of 10 wt % Roystonea-Regia and 5 wt % banana had the highest tensile strength of 64.76MPa, which was attributable to the hydrophilicity and hydration content of the banana fiber. Further flexural and impact experiments confirmed that the influence of water absorption of composites showed a decrement in mechanical properties. The highest impact strength of 45.28 J/m and flexural strength of 75.6MPa were noted for 10 wt % Roystonea-Regia and 5 wt % banana. In addition, Scanning Electron Microscopy (SEM) analysis revealed that alkali treatment improved fiber-matrix interface bonding and roughened fiber surfaces, thereby enhancing the composites' overall performance. The study provides precious insights into the potential of Roystonea-Regia and banana hybrid composites for industrial applications as lightweight, environmentally friendly, and mechanically robust materials.